A Sociolinguistic Perspective on Hausa Loanwords in the Kəlba Language - Mohammed Hamman Barka (Emerging Trends in Languages, 2025)
Linguistic borrowing is seen as a significant source of language development and enrichment. This study examines Hausa loanwords borrowed into the Chadic language of Kəlba, which is spoken in Gombi, Hong, Maiha, Mubi North, and Mubi South local government areas of Adamawa State, Nigeria. The lingua franca in most of northern Nigeria is Hausa, one of the indigenous national languages of the region. The primary sources of data for the study were entries in the) Dictionary of Kəlba Language and recorded interviews with twenty-five (25) native Kəlba speakers from Adamawa State, Nigeria’s Gombi, Hong, Maiha, Mubi North, and Mubi South local government districts. The phonological repair techniques that Kəlba native speakers intentionally or unintentionally utilize to incorporate Hausa loanwords into their vocabulary are the main subject of the analysis. Segmental substitutions, vowel deletion (epenthesis), tone changes, final vowel shortening, and vowel substitution are some examples of Kəlba loan adaptation. Phonological restrictions and the requirement to preserve language coherence within Kəlba are the driving forces behind these modifications. The interaction between Hausa and Kəlba is highlighted in this study, providing insight into the sociolinguistic processes and cross-cultural interactions that affect language acquisition. Additionally, it highlights how Kəlba speakers are flexible in incorporating loanwords, which enhances and evolves the language while maintaining its distinct phonological structure.
Keywords: Hausa loanwords; cross-cultural interactions; linguistic borrowing; phonological repair; sociolinguistics